2013
DOI: 10.1210/jc.2012-3396
|View full text |Cite
|
Sign up to set email alerts
|

RASMutations in Thyroid FNA Specimens Are Highly Predictive of Predominantly Low-Risk Follicular-Pattern Cancers

Abstract: Introduction: RAS mutations are common in thyroid tumors and confer a high risk of cancer when detected in fine-needle aspiration (FNA) specimens. Specific characteristics of RAS-positive thyroid cancers are not well described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
135
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 135 publications
(153 citation statements)
references
References 39 publications
(41 reference statements)
14
135
2
2
Order By: Relevance
“…This is because RAS mutations are consistently found in benign FA, leading some to even suggest that RAS-positive FA should be classified as "false-positive" molecular results [44]. However, this contrasts with the prevailing notion that RAS-positive FA is likely a precursor to RAS-positive follicular-patterned cancer [6,22,23,46].In tumors of follicular cell origin, RAS mutations are essentially restricted to FA, FTC, and FVPTC which are difficult to differentiate as benign or malignant based on cytology alone, and are therefore often indeterminate by FNAB. It is precisely in this group of FNAB results that RAS mutation testing may be most clinically useful.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is because RAS mutations are consistently found in benign FA, leading some to even suggest that RAS-positive FA should be classified as "false-positive" molecular results [44]. However, this contrasts with the prevailing notion that RAS-positive FA is likely a precursor to RAS-positive follicular-patterned cancer [6,22,23,46].In tumors of follicular cell origin, RAS mutations are essentially restricted to FA, FTC, and FVPTC which are difficult to differentiate as benign or malignant based on cytology alone, and are therefore often indeterminate by FNAB. It is precisely in this group of FNAB results that RAS mutation testing may be most clinically useful.…”
mentioning
confidence: 99%
“…A study by Gupta et al in 46 patients with RAS-positive malignancy found bilateral cancer in 43% (n ϭ 20): 45% of these contralateral cancers were positive for RAS mutation, 5% were positive for BRAFV600E, and 50% did not undergo molecular testing. Notably, the majority of patients with bilateral cancer underwent diagnostic lobectomy as their initial procedure, resulting in the need for a second operative procedure in most [23].In some circumstances when the diagnosis of cancer is known preoperatively, total thyroidectomy is indicated. In the case of PTC, central neck dissection may also be considered because of the propensity of PTC to spread to central compartment lymph nodes and its association with recurrent disease [39,57].…”
mentioning
confidence: 99%
“…Importantly, RAS alterations are not specific for thyroid malignant disease, occurring in 20-25% of follicular adenomas (Namba et al 1990, Liu et al 2008. Although follicular adenomas bearing mutated RAS are considered as lesions with high malignant potential (Gupta et al 2013), this strongly hampers the use of RAS status as molecular marker, both in the diagnostic and prognostic setting. To date, prognostic significance of RAS mutations in DTC has been addressed in few studies, with controversial results.…”
Section: Ras Mutationsmentioning
confidence: 99%
“…Sporadic medullary thyroid carcinomas with wild-type RET genes may harbor RAS mutations (HRAS or KRAS). 2,4,5,8,15,16 D. PIK3CA, AKT1, and TP53 Mutational Analysis PIK3CA, AKT1, and TP53 mutations are usually found in advanced thyroid cancer with propensity for dedifferentiation and distant metastasis. 8,17 E. CTNNB1 Mutational Analysis…”
Section: Ras Mutational Analysismentioning
confidence: 99%